2013
DOI: 10.1530/eje-13-0471
|View full text |Cite
|
Sign up to set email alerts
|

Smaller grey matter volumes in the anterior cingulate cortex and greater cerebellar volumes in patients with long-term remission of Cushing's disease: a case–control study

Abstract: Objective: Patients with long-term remission of Cushing's disease (CD) have persistent psychological and cognitive impairments. It is unknown whether, and to what extent, these impairments are accompanied by structural abnormalities in the brain. We aim to investigate structural changes in the brain in patients with predominantly long-term remission of CD and to examine whether these changes are associated with psychological and cognitive dysfunction and clinical severity. Design: A cross-sectional, case-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 54 publications
8
85
0
2
Order By: Relevance
“…Decreasing glucose uptake and the toxic effect of excitatory amino acids on nervous cells are discussed, along with the theory of declining synthesis of neurotrophic factors and the hypothesis that excess glucocorticoids could suppress neurogenesis in the dentate gyrus, leading to hippocampal volume loss. 30 To date only 1 study can be identified that used a similar technique in patients in long-term remission of CD, 3 but not in those with untreated disease. In their study, Andela et al found a significant reduction of volume of the gyrus cinguli in patients after long-term remission of CD, and they hypothesized that these changes play a role in the long-term psychological dysfunction found in patients in whom CD has been cured.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Decreasing glucose uptake and the toxic effect of excitatory amino acids on nervous cells are discussed, along with the theory of declining synthesis of neurotrophic factors and the hypothesis that excess glucocorticoids could suppress neurogenesis in the dentate gyrus, leading to hippocampal volume loss. 30 To date only 1 study can be identified that used a similar technique in patients in long-term remission of CD, 3 but not in those with untreated disease. In their study, Andela et al found a significant reduction of volume of the gyrus cinguli in patients after long-term remission of CD, and they hypothesized that these changes play a role in the long-term psychological dysfunction found in patients in whom CD has been cured.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in cerebellar volume are also known to be caused by elevated cortisol levels and stress, 3,28 which may also facilitate changes in cognitive function and emotional control. 5 Whereas Andela et al found an increase in cerebellar volume in their patients 6 months after cure, our data show a lower cerebellar volume, supporting the results published by Santos et al in 2014, 31 who also found a significant reduction of cerebellar volume in patients with active CS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study did neither describe diagnostic nor remission criteria (20). Described diagnostic criteria were clinical features (truncal obesity, skin and muscle arthophy, moon facies) (11,12,13,21), elevated urinary free cortisol (UFC) (11,12,13,21,22,23,24,25,26,27,28,29), elevated cortisol secretion rates (11,12,13,21,23,24,25,30), elevated midnight salivary cortisol (29,31), absence of blunted circadian rhythm of cortisol secretion (11,12,13,21,26,27,30,32,33), elevated ACTH levels (in CD only) (12,13,21,23,24), lack of suppression after low dose dexamethasone ((1 mg) (22,25,29,33), (2 mg) (12,13,21...…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%